Penguatan Metode Role Model untuk Mengurangi Konflik Antar Siswa Kelas VII SMP X Toboali - Abi Apriyadi (ANWARUL, 2026)
Conflicts among Grade VII junior high school students, particularly in the form of communication misunderstandings and mutual teasing, remain a problem that can disrupt social relationships and the learning process. This study aimed to describe the implementation of the role model method by Guidance and Counseling (GC) teachers in reducing conflicts among Grade VII students at SMP X Toboali. This study used a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and were then analyzed descriptively to describe the exemplary practices of GC teachers in handling student conflicts. The results showed that GC teachers served as role models through polite communication, empathy, and positive conflict resolution. The implementation of the role model method was able to reduce the intensity of conflicts and improve mutual respect among students. The conclusion of this study confirms that the exemplary role of GC teachers is an important strategy in building more positive social behavior in the school environment. The implications of this study indicate the need to strengthen the role of GC teachers as behavioral models in guidance and counseling services to support the creation of a harmonious learning climate.